Sukses Berbisnis Tanpa Bekerja Di Perusahaan: Strategi Berwirausaha Untuk Mahasiswa Non-Karyawan Di Kawasan Industri Bekasi Dan Karawang - Sunarni Sunarni; Asral Asral (Trending: Jurnal Manajemen dan Ekonomi, 2023)
This research discusses entrepreneurial strategies that can be adopted by non-employee students to succeed in the industrial areas of Bekasi and Karawang. These areas are experiencing rapid economic growth, making it an opportune time for students to start their own businesses. The article emphasizes the importance of entrepreneurship education, extracurricular activities, and social capital in supporting these students in establishing successful micro-businesses. The article also explores various business opportunities available in the industrial areas, such as culinary, fashion, technology, and services. It encourages students to think outside the box and develop innovative ideas while providing insights into effective marketing strategies and the use of technology to enhance business competitiveness. The research conducted using a descriptive qualitative method reveals that entrepreneurship education and social capital play an important role in the success of non-employee student businesses. Respondents with a background in entrepreneurship can generate innovative business ideas and effective marketing strategies, while those with strong social networks can access relevant business information and financial support. In addition, mentorship from experienced entrepreneurs helps respondents overcome business challenges. Overall, non-employee students in the industrial areas of Bekasi and Karawang can achieve success by utilizing entrepreneurship education, social capital, and developing innovative business ideas. Effective marketing strategies and the use of technology can also enhance business competitiveness. By doing so, these students can establish successful micro-businesses and contribute to the economic growth of the region.